Green finance in Asia: challenges, policies and avenues for research - Diaz-Rainey, I; Corfee-Morlot, J; Volz, U; Caldecott, B (Taylor & Francis, 2023)
Financing climate change mitigation and adaptation in Asia is critical for its population and economies but also for those of the world. This editorial provides a commentary and overview of ten articles within this special issue of Climate Policy on ‘Green Finance in Asia’. Contributions are diverse in terms of focus and methods. Most of the articles focus on managing transition risk with six of the articles having an energy focus; the dominant themes are the risk of stranded coal assets in China; the role of export finance by China and Japan for fossil fuel-fired power generation assets within Asia; and investment in renewable power generation and the policies to support such investment. The remaining four articles explore various policies in specific country contexts: the effects of green bond policies in China; the greening of monetary policy in China; the governance of sustainable finance in Indonesia; and policies to support investment and finance of off-grid electricity access in Bangladesh. Most of the ten contributions come from researchers in developed countries and principally from non-Asian countries, suggesting there is a need to develop green finance research capability and capacity across Asia. Despite being withing scope of the special issue, this collection does not contain papers on physical risk or adaptation finance. We highlight these as important gaps and priorities for future research.